Academic performance and mathematical processes under a causal model. Correlations found in three public institutions (2020)
This research implemented a model of structural equations aimed at determining the possible causal relationship between the mathematical processes mentioned in the national teachers council mathematics and academic performance in mathematics. The level of development of the mathematical processes promoted by the teacher was analyzed, in students of the fourth to seventh grades of basic education in three public educational institutions of the San José de Cúcuta, Colombia, characterized by obtaining levels of performance (respectively) in the Saber 11 tests of 2018. The sample size was 400 students enrolled in 2019. A questionnaire was proposed and validated that included sociodemographic information of students and then determined the presence and development of the various mathematical processes in classroom work. The results highlight that, of the five mathematical processes, reasoning, representation and problem solving are presented as determining variables of academic performance in students, while the processes of communication and connections are little work in the classroom by teachers. From the results obtained arises as future research, determine what teachers understand by mathematical problems? How do you promote problem solving in the classroom?